2020
DOI: 10.1002/mds.28352
|View full text |Cite
|
Sign up to set email alerts
|

Severity‐Dependent Effects of Parkinson's Disease on Perception of Visual and Vestibular Heading

Abstract: Objectives Parkinson's disease (PD) commonly affects visuospatial navigation causing postural instability and falls. Our overarching aim was to examine the visual and vestibular systems governing visuospatial navigation in PD. We hypothesize that PD affects vestibular and visual motion perception but to a different extent. The effects of PD on motion perception are dependent on the severity of the disease. Methods The two‐alternative‐forced‐choice task objectively measured the motion perception during two expe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 60 publications
0
20
0
Order By: Relevance
“…Our recent study examined the rst part of the hypothesis and the ndings suggested that stimulating the dorsal subthalamic region correlates with vestibular heading perception [8]. Visual heading perception was minimally affected in PD; and DBS did not create a signi cant effect on heading motion perception cued by optic ow [5,8]. Here, we examine the second part of our hypothesis and test if STN DBS induced activations of white-matter pathways create the change we observed vestibular heading perception of subjects with PD.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Our recent study examined the rst part of the hypothesis and the ndings suggested that stimulating the dorsal subthalamic region correlates with vestibular heading perception [8]. Visual heading perception was minimally affected in PD; and DBS did not create a signi cant effect on heading motion perception cued by optic ow [5,8]. Here, we examine the second part of our hypothesis and test if STN DBS induced activations of white-matter pathways create the change we observed vestibular heading perception of subjects with PD.…”
Section: Resultsmentioning
confidence: 99%
“…For left-sided heading, the observed improvement occurred when VTA center was located more anterior and dorsal to the STN in the contralateral hemisphere. This is an important insight because left is the direction that is impaired most in PD in a severity-dependent matter [5]. Left is also the motion direction that current stimulation settings appear to create minimal improvement [8].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations